1954
DOI: 10.1084/jem.100.6.629
|View full text |Cite
|
Sign up to set email alerts
|

Studies on a Lipoproteinase of Group a Streptococci

Abstract: A streptococcal enzyme which causes opalescence in serum was described by Ward and Rudd in 1938. These authors found that the enzyme was produced by many types of group A streptococci, but not by streptococci belonging to other groups. Seitz filtrates of serum broth cultures of active strains produced opalescence in rabbit, mouse, or human sera. These authors postulated that the enzyme altered serum protein but found no evidence to substantiate their theory (1).The studies reported in this paper were undertake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

1963
1963
1981
1981

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 7 publications
0
29
1
Order By: Relevance
“…The production of opacity in horse serum by group A streptococci is believed to be mediated by a lipoproteinase which acts upon the a,-lipoprotein fraction of the serum (Krumwiede, 1954;Rowen & Martin, 1963). Streptococci of groups other than A apparently do not produce opacity in serum, and within group A the serum opacity reaction (s.0.r.)…”
Section: Introductionmentioning
confidence: 99%
“…The production of opacity in horse serum by group A streptococci is believed to be mediated by a lipoproteinase which acts upon the a,-lipoprotein fraction of the serum (Krumwiede, 1954;Rowen & Martin, 1963). Streptococci of groups other than A apparently do not produce opacity in serum, and within group A the serum opacity reaction (s.0.r.)…”
Section: Introductionmentioning
confidence: 99%
“…Krumwiede (1954) and Rowen (1961) stated that in serum-free media the enzyme was cell bound with no extracellular activity. In initial studies with AN 124 we could find no extracellular enzyme activity, but subsequent studies have indicated that with certain strains some activity can be found in the supernatant, even when serum-free broth is used (L. W. Wannamaker, S. Skjold & F. H. Top, unpublished observations).…”
Section: Resultsmentioning
confidence: 99%
“…Extraction of the enzyme in a cell-free state Krumwiede (1954), Rowen (1961) and Rowen & Martin (1963) obtained the enzyme in a soluble form by extraction of whole cells with urea. In their hands this gives a product of high activity and considerable stability.…”
Section: Resultsmentioning
confidence: 99%
“…This serum opacity reaction (SOR) is mediated by a factor (OF) which acts upon the ccl-lipoprotein fraction of serum (Krumwiede, 1954).…”
Section: Introductionmentioning
confidence: 99%